Pathogenic gain-of-function mutations in the prodomain and C-terminal domain of PCSK9 inhibit LDL binding - Sarkar, Samantha K.; Matyas, Angela; Asikhia, Ikhuosho; Hu, Zhenkun; Golder, Mia; Beehler, Kaitlyn; Kosenko, Tanja; Lagace, Thomas A. (Frontiers in Physiology, 2022)
Proprotein convertase subtilisin/kexin type-9 (PCSK9) is a secreted protein that binds and mediates endo-lysosomal degradation of low-density lipoprotein receptor (LDLR), limiting plasma clearance of cholesterol-rich LDL particles in liver. Gain-of-function (GOF) point mutations in PCSK9 are associated with familial hypercholesterolemia (FH). Approximately 30-40% of PCSK9 in normolipidemic human plasma is bound to LDL particles. We recently reported that an R496W GOF mutation in a region of PCSK9 known as cysteine-histidine–rich domain module 1 (CM1) prevents LDL binding in vitro [Sarkar et al., J. Biol. Chem. 295(8), 2285–2298 (2020)]. Herein, we identify additional GOF mutations that inhibit LDL association, localized either within CM1 or a surface-exposed region in the PCSK9 prodomain. Notably, LDL binding was nearly abolished by an S127R GOF mutation, one of the first PCSK9 mutations identified in FH patients. PCSK9 containing alanine or proline substitutions at amino acid position 127 were also defective for LDL binding. LDL inhibited cell surface LDLR binding and degradation induced by exogenous PCSK9-D374Y but had no effect on an S127R-D374Y double mutant form of PCSK9. These studies reveal that multiple FH-associated GOF mutations in two distinct regions of PCSK9 inhibit LDL binding, and that the Ser-127 residue in PCSK9 plays a critical role.